The effect of technological intensity of exports on the economic growth of Brazilian microregions: A spatial analysis with panel data - Augusta Pelinski Raiher; Alex Sander Souza do Carmo; Alysson Luiz Stege (EconomiA, 2017)
The objective of this study was to analyze empirically the effects of exports segmented into technological levels on the economic growth of Brazilian microregions during the period 2000–2010 in light of the Crespo-Cuaresma and Wörz's (2005) model. The hypothesis is that exports increase economic growth due to the productivity differential existing between the exporting and non exporting sectors and the positive externality generated by the exporting in the non exporting sector. Theoretically, the higher technology the exported goods have, the stronger these effects are. By classifying the exports into technological levels and estimating the empirical model using the spatial data panel technique, with fixed effect, the two central hypotheses in the Crespo-Cuaresma and Wörz's (2005) model were validated, with a productivity differential in all exporting segments, and also with a subsequent effect of externalities on the economic dynamism. This effect might go beyond territorial limits mainly when the goods exported belong to the low and mid-low technology industry. Also, a differentiated effect was observed regarding the external insertion in the economic growth of the regions with high exports vs. those with low participation in the international trade. In the former, the most intense indirect effect is mainly related to products with higher aggregated value, while in the latter more effects are seen mainly linked to the exportation of non-industrial products.
Keywords: 330; Economic growth; Exports; Technological intensity; Microregions; Crescimento econômico; Exportaç\~oes; Intensidade tecnológica; Microrregi\~oes